Siphonophoridae from Brazilian Amazonia Part 1 – The genus Columbianum Verhoeff, 1941 (Diplopoda, Siphonophorida) - Read, Helen J.; Enghoff, Henrik (European Journal of Taxonomy, 2018)
A large sample of Siphonophoridae from Brazil was studied; two morphological groups could be distinguished. Here species considered to be from the genus Columbianum Verhoeff, 1941 are examined in detail. The genus is known from Central and South America (Guatemala, Panama, Honduras, Guiana, Colombia, Peru and Brazil) and is characterised by a clear demarcation between head and rostrum in combination with long antennae, clearly surpassing the tip of the rostrum. A list of previously described species considered to belong to the genus is given; three new species are described: C. major sp. nov. has a large body size and a small head, C. nahvalr sp. nov. has a particularly pronounced domed head and a more castellated appearance to the body, C. adisi sp. nov. has a small body size and a very characteristic hind margin to the pleurites. Variation in the state of preservation of specimens hinders a diagnosis, but the examination of the accessory claw and details of the metazonital limbus and pleurite edges are helpful. Unusually for Diplopoda, the male gonopods are not very useful for identification. Ecological comments are given for each new species, one of which, C. adisi sp. nov., is from the seasonally flooded forest and appears to avoid inundation by climbing trees.